2001
DOI: 10.1149/1.1375170
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Characteristics of Hydrogen-Damaged  ( Pb , La )  ( Zr , Ti )  O 3 Capacitors with Pt and IrO2 Top Electrodes

Abstract: The effect of hydrogen on ferroelectric properties was investigated for ͑Pb, La͒͑Zr, Ti͒O 3 ͑PLZT͒ films with Pt and IrO 2 top electrodes. The P-E hysteresis loop and fatigue properties of the Pt/PLZT/Pt capacitor are completely recovered by recovery anneal at 700°C in O 2 ambient after a hydrogen-forming gas anneal. On the other hand, IrO 2 /PLZT/Pt capacitor after recovery anneal does not show a complete recovery for ferroelectric properties. The IrO 2 top electrode in the IrO 2 /PLZT/Pt capacitor is complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, an as-grown IrO 2 top electrode was easily reduced to Ir metal by hydrogen annealing at 300°C which simulates the process conditions for interlayer-dielectric deposition. 12 Aggarwal et al reported that even a bare La 0.5 Sr 0.5 CoO 3 ͑LSCO͒ top electrode can prevent the complete loss of ferroelectricity during forming gas treatment. 13 The conducting oxide, ͑Ba,Sr͒RuO 3 ͑BSR͒, 14,15 which has many advantages for BST due to their similarity in crystal structure and chemical composition, was evaluated as an electrode for high dielectric capacitors.…”
mentioning
confidence: 99%
“…However, an as-grown IrO 2 top electrode was easily reduced to Ir metal by hydrogen annealing at 300°C which simulates the process conditions for interlayer-dielectric deposition. 12 Aggarwal et al reported that even a bare La 0.5 Sr 0.5 CoO 3 ͑LSCO͒ top electrode can prevent the complete loss of ferroelectricity during forming gas treatment. 13 The conducting oxide, ͑Ba,Sr͒RuO 3 ͑BSR͒, 14,15 which has many advantages for BST due to their similarity in crystal structure and chemical composition, was evaluated as an electrode for high dielectric capacitors.…”
mentioning
confidence: 99%